DETERMINAN PERTUMBUHAN EKONOMI DI NEGARA OKI (STUDI KASUS: 10 NEGARA ANGGOTA OKI) - Fani Monada Putri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
Economic growth is a leading indicator in measuring a country's well-being. Economic growth in most countries in the world has increased so far. Therefore, the purpose of this study is to find out the factors that affect economic growth in OIC member countries. The study also aims to determine economic growth in 10 OIC member countries. The results showed that export variables, government spending, human development indices had a significant positive effect on economic growth in the 10 OIC member countries. While the population growth variable, the labor force variable has a significant negative effect on economic growth in the 10 OIC member countries. The variables of the democracy index have no effect on economic growth in the 10 OIC member countries.